Overview of Menarche, Menstruation and Menstrual Hygiene - Chakor, Ganesh; Deshpande, Rupali; Morane, Dharmraj (Innovational: Journal of Nursing and Healthcare, 2024)
Each child undergoes many changes when the growth and development take place over a period of time. These development changes are common among both girls and boys; one of such physiological changes among girl is attaining menarche. It makes beginning of a multiple of physical, physiological, and psychological changes in the lives of the adolescent girls. In general, menarche indicates the girl’s maturity and the readiness for marriage and sexual activity. Puberty is a period of rapid physical and personality growth. A girl has entered puberty when she begins to menstruate (Menarche). Puberty for girls is the period for her sexual maturity. There is very little awareness about menstruation among girls when they first experience it. Social prohibitions and negative attitude of elders in discussing the related issues openly have blocked the access of adolescent girls to the right kind of information especially in rural, urban, and tribal community. In first period, more importance must be given to starting of menstruation in women life. To highlight the menstrual hygiene awareness among girls, May 28, is observed as menstrual hygiene day, which aims to break taboos and raise awareness about the importance of good menstrual hygiene management for women and adolescent girls worldwide. Thus, menstrual hygiene practices are greatly emphasized among school girls to promote the reproductive health, which also improves the girl’s self-image and promote their attitude toward good reproductive health. It also avoids the embarrassment of staining their cloth and promote their self-respect among their friends. Good menstrual hygiene enhances their confidence and promote the regular school attendance and prevent environmental pollution. In this review, we will discuss about menarche, menstruation, menstrual hygiene, and knowledge, attitude, and practice about menstruation.